2010
DOI: 10.1021/cm100926r
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Tantalum(V) Oxide Films by Atomic Layer Deposition Using the Highly Thermally Stable Precursor Ta(NtBu)(iPrNC(Me)NiPr)2(NMe2)

Abstract: The atomic layer deposition (ALD) growth of Ta 2 O 5 films was demonstrated using Ta(NtBu)-(iPrNC(Me)NiPr) 2 (NMe 2 ) and water with substrate temperatures between 225 and 400 °C. At 325 °C, self-limited growth was demonstrated with Ta(NtBu)(iPrNC(Me)NiPr) 2 (NMe 2 ) and water pulse lengths of g0.5 s. An ALD window was observed between 275 and 350 °C, with a growth rate of 0.28 A ˚/cycle. The growth rates were 0.33 and 0.37 A ˚/cycle at 250 and 225 °C, respectively. At 375 and 400 °C the growth rate increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Interestingly, the phase was also absent when the 50 nm Ta 2 O 5 film was annealed at 750 °C (Supporting Information, Figure S2). No crystalline Ta 2 O 5 was observed in any of our annealing experiments, although the material has been reported to crystallize at 700 °C and above. , …”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, the phase was also absent when the 50 nm Ta 2 O 5 film was annealed at 750 °C (Supporting Information, Figure S2). No crystalline Ta 2 O 5 was observed in any of our annealing experiments, although the material has been reported to crystallize at 700 °C and above. , …”
Section: Resultsmentioning
confidence: 61%
“…No crystalline Ta 2 O 5 was observed in any of our annealing experiments, although the material has been reported to crystallize at 700 °C and above. 23,24 Our first experiments revealed that annealing temperatures higher than 750 °C can lead to lithium silicate formation since the stacks are deposited onto single crystalline silicon (Supporting Information Figure S1). In most of the later experiments, temperatures below 700 °C were used for annealing.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…An alkylamide‐imide‐amidinate compound, t BuN = Ta(N i PrC(Me) i PrN) 2 (NMe 2 ) was investigated for the ALD of Ta 2 O 5 , together with water as the oxygen source. Self‐limiting growth was confirmed at 325°C with a rather low GPC of 0.28 Å per cycle.…”
Section: Ald Of Groups 4 and 5 Oxide Thin Filmsmentioning
confidence: 99%
“…The decomposition temperature of a precursor is often close to the upper temperature limit of the ALD window in an ALD process. 69,70 This similarity can be used to perform an initial comparison of previous precursors with 10− 15.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is difficult to compare the precursor properties of the compounds in the present work with those of precursors that have been previously used in the ALD of lanthanide-containing thin films, however, since precursor decomposition temperatures are rarely given. The decomposition temperature of a precursor is often close to the upper temperature limit of the ALD window in an ALD process. , This similarity can be used to perform an initial comparison of previous precursors with 10 – 15 .…”
Section: Resultsmentioning
confidence: 99%